The Impact of White LEDs in Environmental Lightening on Energy Savings - Huseynov, I.T. (Herald of Azerbaijan Engineering Academy, 2021)
The presented work is devoted to the study of the prospects for the introduction of white LEDs and was discussed in the context of world ecology and obtaining a large economic effect. Up to 20% of the electricity produced in the world is spent on lightening and, being a rather serious indicator, it can be significantly reduced using white light diodes (LEDs) and other modern technologies. For this reason, in this work, the prospects for the use of white LEDs in the lightening system were investigated. In the presented work, the issue of the manufacture of white LEDs is deeply considered, the necessary main part of which is the phosphor material, because the choice of the phosphor in this direction in the manufacture of highly efficient and permanent systems is one of the main problems. It is known that rare earth materials and their compounds are basic in matrix materials and with the choice, give highly effective results. In various industries and technologies, especially in the field of lightening, the prospects for white light diodes and similar systems have been studied in aspects of ecology and economic benefits.